Pinning of Ferromagnetic Domains in Interconnected Pentagonal Spin Ice Lattices - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2019)
The magnetization reversal process of interconnected pentagonal spin ice systems was investigated using micromagnetic simulations and experimental measurements. Five different systems were investigated, beginning with the interconnected Shakti lattice and introducing deformations with the idea of obtaining pentagonal tiling (belonging to the P4 group) until reaching an interconnected square lattice. In all pentagonal lattices, ferromagnetic domains are pinned, acting as isolated domains in an antiferromagnetic lattice, with Cairo tiling being the lattice that allows pinning more domains. Experimental measurements on a Cairo lattice of larger dimensions show that the shape of the hysteresis curve is invariant to the size of the bars that make up the interconnected pentagonal spin ice systems. © 2019 Elsevier B.V.